Pengetahuan dan Adaptasi Petani Kopi terhadap Perubahan Iklim di Kecamatan Air Hitam Kabupaten Lampung - Abdul Mutolib; Ali Rahmat; Tita Sumiati (Fakultas Teknik, 2021)
Climate change has caused production declines and crop failures in some agricultural commodities. This study aims to identify the level of knowledge, adaptation practices, and types of protective trees used by coffee farmers in dealing with climate change. The research was carried out in Rigis Jaya Village, West Lampung District from May to July 2021. The number of respondents was 80 coffee farming households. Respondents were determined through a simple random sampling approach. The data collected consists of qualitative and quantitative data. Data collection was carried out through the survey method. The results of the study illustrate that coffee farmers have realized that climate change has occurred. 60% of coffee farmers are aware of climate change in the last 1-5 years and 20% of coffee farmers are more than 5 years old. From mitigation practices, 25% of coffee farmers mitigate climate change. Climate change mitigation practices carried out by farmers are through the use of superior coffee varieties, planting shade trees, setting coffee spacing, making vents, and utilizing the remaining coffee husks to increase soil fertility and moisture. There are 14 types of shade trees planted by farmers consisting of legumes and non-legume trees. Petai (Parkia speciosa) is the most widely planted shade tree in coffee plantations with 45% of the total respondents.